Pengaruh Penggunaan Media Pembelajaran Digital Berbasis “Assemblr Edu” Terhadap Hasil Belajar Peserta Didik Pada Materi Keragamaan Budaya Indonesia Mata Pelajaran Ipas Kelas IV SDN Sidokumpul - Wulandari, Oktavia Wulandari; Rozy, Fakhrur (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to examine the effect of using the digital learning media "Assemblr Edu" on student learning outcomes in the topic of Indonesia's cultural diversity in the IPAS subject for fourth-grade students at SDN Sidokumpul. The research employed a quantitative approach with a quasi-experimental design using a one-group pretest-posttest design. A total of 33 students participated as research subjects. Data were collected through written tests administered before and after the implementation of Assemblr Edu. The results of the Wilcoxon Signed Ranks Test showed a significance value of 0.000 (<0.05), indicating a statistically significant difference between pretest and posttest scores. All students demonstrated an increase in learning outcomes after the intervention. These findings confirm that the use of Assemblr Edu effectively enhances students’ understanding of the material. The study supports Jerome S. Bruner’s cognitive learning theory, emphasizing that active student involvement and interactive media improve comprehension and engagement. Therefore, Assemblr Edu is recommended as an innovative learning medium to support 21st-century learning objectives in elementary schools.